0101 Evolution of a cost effective reusable ultrasound guided central venous cannulation training simulation model. (2nd November 2015) - Hall, Alexander; Barr, Patrick De; Willers, Johann; Mitchell, Sean; Staniforth, Matthew; Turner, Julie
Abstract : Background: NICE guidelines mandates use of ultrasound guided central venous cannulation (USGCVC). This gave rise to the need for a realistic, effective and cost-effective training tool to teach this skill, as available trainers were expensive and did not survive dilation and actual cannulation. Over several years we have developed and used a simulation model that we think fulfils this function. Description of innovation: We evaluated numerous venous surrogates and found latex racing cycle inner tube to have the same dimensions, ultrasonic appearance, haptic characteristics and resealability as central veins. 1 This was used initially in a gelatine substrate which was repaired after use. After developing an Ispagula husk gel based medium that was self-repairing after dilation we switched to that. 2 Both these mediums suffered from desiccation and fungal colonisation, which was solved by adding a preservative to create ADAMgel (A queous D ietary fibre A ntifreeze M ix gel). We combined the vessel and soft tissue analogue in existing manikins or food containers under a simulated skin. Also included was a pulsatile arterial simulator. The latex tubing was connected to a reservoir of coloured fluid under the correct pressure. Cost were £5–£10 per model. Outcomes: These models were then used in formal teaching on USGCVC workshops for medical students, 3 junior doctors 4 and Advanced Trauma and Life Support (ATLS) courses. They remained fully functional resealing after dilation and sonographically pristine without producing needletracts. Trainees scored them over 95% for realism, utility and models' ability to remain fully functional without producing needletracts, with all participants recommending the model for teaching. 4 Simulated skin analogue had to be periodically replaced and probably eventually the latex inner tubing as well. Take home messages: USGCVC simulation based training can be effectively provided at a reasonable cost enabling trainees to fulfil requirements for specialisation training. References: Shaw C, Willers J, Bukunola B, et al . Searching for a superior central venous surrogate for ultrasound simulation. Anaesthesia 2013:68 :43 Barnes L, Willers J, Hariharan S, et al . Gauging the gel in Fybogel. AABGI Annual Congress. Anaesthesia 2014;69 :s4.11–88 Akrimi S, Malley T, Willers J, et al . A training day for undergraduate students using practical workshops combined with theatre sessions to teach essential skills and inspire interest in anaesthetics. Anaesthesia 2014, 69 :31 Hall A, De Barr P, Willers J, et al . Does simulation increase the familiarity of non-anaesthetists with central venous cannula insertion? Sent to AABGI Annual Congress, 2015